The Burnout among medical students in Poland – a review article - Cegiełka, Patryk; Pal, Adrian; Cienkowski, Krzysztof; Katra, Małgorzata; Szczęsny, Mikołaj; Żeżawska, Karolina; Głowacka, Izabella; Ślot, Marcin; Adamczyk, Aleksandra; Sicińska , Maria (Journal of Education, Health and Sport, 2026)
Burnout, defined in the ICD-11 classification as a response to chronic stress, is characterized by feelings of exhaustion, mental distancing from work, and a reduced sense of professional efficacy. This paper summarizes previous publications regarding the scale of this phenomenon, its symptoms, and coping strategies among medical students in Poland, compared with international data. The review indicates that the problem is global and increasing in magnitude— in Poland, up to 53% of students may exhibit symptoms of exhaustion, and 42% struggle with burnout, with higher rates observed among women and senior students. The article discusses the symptomatology of the syndrome, including somatic symptoms such as headaches and fatigue, as well as psychological manifestations, including cynicism, depersonalization, and impostor syndrome. Coping strategies are also presented, contrasting destructive methods (substance use, social isolation) with effective preventive techniques such as mindfulness training, cognitive reinterpretation of mistakes, and peer support.